Single Ophthalmology Program Trends in Resident Surgical and Research Productivity by Gender, Underrepresented Minority Status, and Welcoming a Child - Kong, Alan W.; Schallhorn, Julie M.; Ou, Yvonne (Journal of Academic Ophthalmology, 2021)
Objective The aim of the study is to identify differences for cataract surgery, total procedural volume, and publication rates between residents by gender, underrepresented minority (URM) status, and welcoming a child during ophthalmology residency.Design This is a retrospective, cross-sectional study.Participants A total of 89 residents graduating from 2002 to 2020 at a single program were included.Methods A multiple linear regression model was created to determine factors predictive of the number of cataract surgeries performed as the primary surgeon, total procedural volume, number of publications, or first author publications. Independent variables included resident gender, URM status, PhD degree, welcoming a child during residency, and graduation year.Results Of the 89 graduating residents included in this study, identifying as female (45 women, 50.6%) and as URM (eight identifying as URM, 9.0%) was not associated with a difference in surgical or research volume. Female residents performed a mean (SD) of 240.1 (55.1) cataract surgeries while male residents performed 210.6 (46.1) cataract surgeries. Residents identifying as URM completed 228.1 (41.9), while non-URM residents completed 234.8 (51.9) cataract surgeries. Since 2008, eight female residents (22.2%) and two male residents (6.9%) added children to their families. Welcoming a child to the family was also not associated with decreased surgical or publication volume. Number of cataract surgeries, total procedures, and number of publications did increase over time (p <0.001), as each graduation year was associated with 5.4 (95% CI: 3.9, 7.1) more cataract surgeries and 30.5 (95% CI: 25.7, 36.9) more procedures. Each year was also associated with 0.24 (95% CI: 0.09, 0.38) more publications and 0.18 (95% CI: 0.08, 0.28) more first author publications.Conclusion Surgical and research productivity has increased, and female residents and residents who identify as URM did not have fewer cataract surgeries or procedures. Welcoming a child also did not correlate with differences in surgical or procedural volume. Programs should continue to promote equitable surgery and procedural distributions as well as identify more targeted strategies to encourage and recruit underrepresented medical students into ophthalmology.
Keywords: ophthalmology; surgical volume; cataract surgery; publication rate; gender; underrepresented minority